M. Petkevičiaus katekizmo (1598 m.) tarmė - Zinkevičius, Zigmas (Baltistica, 1971)
THE DIALECT OF M. PETKEVIČIUS CATECHISM (1598)The article deals with the dialect of the Lithuanian Calvinist Catechism published by M. Petkevičius (Pietkiewicz) in 1598. The analysis is focused on the main dialect features peculiar to the Catechism and the dialect itself is localized as belonging to the vicinity of Kėdainiai (see plan in Baltistica, VI, 2, p. 229). Some minor features of other dialects (East High Lithuanian, possibly Samogitian) are dealt with as well. The scope of change of the dialect under consideration (from the 16th century up to our days) is analysed.It is stated that in the environs of Kėdainiai at the end of the 16th century the nasal vowels were still retained, the consonants k, g, š, ž, č, (dž) alone were more clearly palatalized before the vowels of the e-type, the distribution of en, in ‖ ę, į and ł ‖ l was more archaic than it is now. Of the later dialect innovations the following are more important: monophthongization of uo and ie and the reduction of long vowels in unstressed syllables, the loss of many relic forms, e. g. dual, illative, adessive, allative, supine, athematic verbs, the levelling of various doublet and parallel forms, e. g. the root deiv- and diev-, the suppletive paradigm of the third personal prounoun, the smoothing of declension types, the loss of pronominal adjectives, many vivid vocabulary changes.A great influence of the Kėdainiai dialect on Lithuanian writings of the 16th and 17th centuries is emphasized.
Keywords: Petkevičius; katekizmas; senieji raštai; tarmė